Penerapan Kaidah Muamalah dalam Transaksi Ekonomi Digital: Tinjauan Pustaka pada Paylater, E-Wallet, dan Marketplace - Aulia Rahmi; Mustofa Hasan; Harmanto Raharjo; Alfarid Hilman (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2025)
This study aims to analyze the application of fiqh muamalah principles in modern digital financial systems, particularly on paylater, e-wallet, and marketplace platforms. The research focuses on assessing the conformity of digital transactions with Islamic legal principles, namely clarity (bayān), justice (‘adl), and the avoidance of riba, gharar, and maysir. The research employs a qualitative-descriptive library method, analyzing scholarly journals and relevant Islamic finance fatwas from 2020–2025. The findings indicate that paylater systems comply with Sharia if they employ the bai‘ bi tsaman ājil contract without interest or time-based penalties. E-wallet platforms are permissible when free from hidden charges and uphold transparency in user rights and obligations. Likewise, marketplace operations are Sharia-compliant if they ensure clarity of contract objects, fair pricing (thaman al-mithl), and consumer protection (ḍamān). In conclusion, digital financial innovations can be harmonized with Islamic law when grounded in the principles of al-‘ibrah fī al-mu‘āmalāt bimā fī nafs al-amr and al-ma‘rūf ‘urfan kal-mashrūṭ sharṭan, thus aligning with the objectives of Sharia (maqāṣid al-syarī‘ah).